Language learning strategies: An holistic view - Griffiths, Carol; Cansiz, Gökhan (Studies in Second Language Learning and Teaching, 2015)
The language learning strategy question has been debated on a number of levels, including definition, the strategy/success relationship and strategy coordination. In addition, awareness has been steadily growing of the importance of taking an holistic view of the strategy phenomenon and examining strategies not just in isolation but as part of an overall picture which includes learning situation, learning target and individual learner characteristics. This article will first of all review the literature and the previous research on these controversial issues, and suggest a workable definition. Then, in order to illustrate the importance of such an holistic view, the results of a small scale study which looks at the strategies used by 16 successful language learners who were all either teaching English or teaching in English at university level will be reported. The quantitative results indicated that these successful learners used many strategies, especially those that suited their goals and their situations; they also frequently used and carefully orchestrated strategy repertoires which suited their own individual needs. The responses of one highly successful respondent were also examined qualitatively. The implications of these findings and the importance of viewing learners holistically are discussed and suggestions are made for ongoing research.